2000
DOI: 10.1177/03635465000280041301
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Sizing of Meniscal Allografts in Meniscus Transplantation

Abstract: The purpose of this study was to determine the accuracy of radiographic and magnetic resonance imaging techniques in preoperative sizing for allograft meniscus transplantation. Twelve cadaveric knee specimens underwent sequential radiographs, magnetic resonance imaging scans, and arthrotomy. Meniscus dimensions were measured in multiple planes for the purpose of determining accuracy of imaging studies in comparison with actual meniscus dimensions. Overall, magnetic resonance imaging proved only slightly more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
136
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 19 publications
3
136
0
1
Order By: Relevance
“…Medial tibial plateau length (MTPL) was measured from the maximum AP dimension of the medial plateau in a radiographic lateral view [14,15]. Anteroposterior radiography was used to measure medial tibial plateau width (MTPW) by obtaining the distance from the medial margin of the tibial plateau to the peak of the medial intercondylar eminence [14,15].…”
Section: Measurement Of Bony Landmarks and Medial Meniscal Sizesmentioning
confidence: 99%
See 1 more Smart Citation
“…Medial tibial plateau length (MTPL) was measured from the maximum AP dimension of the medial plateau in a radiographic lateral view [14,15]. Anteroposterior radiography was used to measure medial tibial plateau width (MTPW) by obtaining the distance from the medial margin of the tibial plateau to the peak of the medial intercondylar eminence [14,15].…”
Section: Measurement Of Bony Landmarks and Medial Meniscal Sizesmentioning
confidence: 99%
“…Anteroposterior radiography was used to measure medial tibial plateau width (MTPW) by obtaining the distance from the medial margin of the tibial plateau to the peak of the medial intercondylar eminence [14,15]. Imaging evaluation was performed using an Achieva 1.…”
Section: Measurement Of Bony Landmarks and Medial Meniscal Sizesmentioning
confidence: 99%
“…The most common sizing method is the use of preoperative anterior-posterior and lateral plain radiographs [6,55], although MRI [56,57] and CT scans [58] have also been employed. Plain radiographs take into account bony landmarks, and the most commonly used method has been described by Pollard et al [55].…”
Section: Graft Sizingmentioning
confidence: 99%
“…Some studies have found that a reduction of 5% of the meniscal size determined by the Pollard method reduces the percentage of meniscal extrusion with no adverse effect on clinical and radiographic outcomes [43]. Despite plain radiograph are more commonly used for graft sizing [6], some studies have demonstrated that the use of MRI is more accurate than plain radiographs [56,57]. An oversized and undersized graft increases forces across the articular cartilage and allograft, respectively [59].…”
Section: Graft Sizingmentioning
confidence: 99%
“…Using this ability, four contact points representing the anterior and posterior horns of the lateral and medial menisci are defined on the tibia segment (Fig. 7) [52]. A simple constraint preventing lateral displacement of the tibia with respect to the femur is also defined.…”
Section: Modeling Of the Knee Jointmentioning
confidence: 99%